2021
DOI: 10.1016/j.isci.2021.102076
|View full text |Cite
|
Sign up to set email alerts
|

The endocytosis of oxidized LDL via the activation of the angiotensin II type 1 receptor

Abstract: Summary Arrestin-dependent activation of a G-protein-coupled receptor (GPCR) triggers endocytotic internalization of the receptor complex. We analyzed the interaction between the pattern recognition receptor (PRR) lectin-like oxidized low-density lipoprotein (oxLDL) receptor (LOX-1) and the GPCR angiotensin II type 1 receptor (AT1) to report a hitherto unidentified mechanism whereby internalization of the GPCR mediates cellular endocytosis of the PRR ligand. Using genetically modified Chinese hamste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 64 publications
5
28
0
Order By: Relevance
“…In addition, the excess of lipid uptake by macrophages perpetuates the inflammatory response, and oxLDLs induce signaling cascades that activate NF-kB targets [ 152 , 153 , 154 ], which maintain EC activation, monocyte recruitment, and foam cell formation [ 146 ]. The uptake of oxLDLs by macrophages could be considered a protective mechanism, as they remove cytotoxic elements from the intima.…”
Section: Atherosclerosis Initiation and Fatty Streak Formationmentioning
confidence: 99%
“…In addition, the excess of lipid uptake by macrophages perpetuates the inflammatory response, and oxLDLs induce signaling cascades that activate NF-kB targets [ 152 , 153 , 154 ], which maintain EC activation, monocyte recruitment, and foam cell formation [ 146 ]. The uptake of oxLDLs by macrophages could be considered a protective mechanism, as they remove cytotoxic elements from the intima.…”
Section: Atherosclerosis Initiation and Fatty Streak Formationmentioning
confidence: 99%
“…LOX-1 is an important receptor of oxLDL uptake in endothelial cells (Mango et al, 2011;Akhmedov et al, 2014;Barreto et al, 2021) but is also able to bind acLDL at comparable affinity (Kumano-Kuramochi et al, 2012). Other oxLDL-related known receptors are, e.g., the scavenger receptor CD36, the scavenger receptor class A member 1 (SCARA1), and the Gprotein-coupled receptor angiotensin II type 1 receptor (AT1) (Silverstein, 2018;Pandey et al, 2020;Cheng et al, 2021;Takahashi et al, 2021). Previously, E. bovis-infected host cells have been shown to upregulate LOX-1 gene transcription during first merogony (Taubert et al, 2010;Hamid et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that a pattern recognition receptor (PRR), lectin-like oxidized low-density lipoprotein (oxLDL) receptor (LOX-1) and a GPCR, angiotensin II type 1 receptor (AT1) form a complex ( Yamamoto et al., 2015 ) and that the cellular uptake of oxLDL was mediated by β-arrestin-dependent endocytosis of AT1 ( Takahashi et al., 2021 ). The interaction of the receptors was supported by experiments including immunoprecipitation, in situ PLA assay ( Yamamoto et al., 2015 ) and live-cell imaging of the two receptors ( Takahashi et al., 2021 ). Here, we provide a protocol of the latest experiment that will allow for live-cell imaging of endocytosis of the two adjacent membrane receptors, LOX-1 and AT1 in a single cell ( Takahashi et al., 2021 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…We have applied this protocol to imaging of endocytosis of the LOX-1 and AT1 in CHO-K1 cells, but the protocol can be applied to a variety of membrane receptors in other cell lines. For complete details on the use and execution of this protocol, please refer to Takahashi et al. (2021) .…”
mentioning
confidence: 99%
See 1 more Smart Citation